Spatial and temporal variability in positive and negative plant–bryophyte interactions along a latitudinal gradient. (14th December 2012) - Doxford, Simon W.; Ooi, Mark K. J.; Freckleton, Robert P.; Brooker, Rob
Summary According to the Stress Gradient Hypothesis, facilitation and competition are considered to be important at opposite ends of an environmental gradient. However, recent research has questioned the generality of this idea. One limitation is that the small‐scale and short‐term nature of much research into plant interactions limits our understanding of how their strength and importance changes over large temporal and spatial scales. Here, we experimentally measured the interactions between bryophytes and a community of winter annuals in sand dunes along a c. 1500 km latitudinal gradient over two generations. We carried out bryophyte‐removal experiments within permanent quadrates at eight field sites along the Atlantic coast of Western Europe, to measure the spatio‐temporal variation in the strength and direction of biotic interactions. We found a striking contrast in the nature of plant–bryophyte interactions observed in consecutive years of study, using three measures of plant demographics: density, plant performance and population growth. In the first year facilitation dominated, but showed an overall decline in strength from south to north. In the following year facilitation was largely replaced by competition, which also declined in strength from south to north along the latitudinal gradient. Interaction strengths are correlated with population growth rate, so that facilitation dominated in sites and years where population growth was low, whereas when population growth was high competition appeared to be more important. This is consistent with the Stress Gradient Hypothesis, but further to previous studies we demonstrate that this mechanism operates over time and in terms of population growth rates. The effects of bryophyte removal were more strongly related to population density and population growth than to individual plant performance (i.e. reproductive output). This result suggests interactions are most important during germination and early establishment of annuals, and not in terms of inter‐plant competition for resources. Synthesis: This study is one of the first to show that there may be extreme spatio‐temporal variation in the strength and direction of interactions, with substantial changes in their impact over a short time period. Our results suggest that the Stress Gradient Hypothesis may operate within and along gradients, as well as inter‐annually. This may therefore play a role in buffering population dynamics.